Incremental distribution of strontium and zinc in great ape and fossil hominin cementum using synchrotron X-ray fluorescence mapping. Issue 138 (31st January 2018) - Dean, Christopher; Le Cabec, Adeline; Spiers, Kathryn; Zhang, Yi; Garrevoet, Jan
Abstract : Cementum and the incremental markings it contains have been widely studied as a means of ageing animals and retrieving information about diet and nutrition. The distribution of trace elements in great ape and fossil hominin cementum has not been studied previously. Synchrotron X-ray fluorescence (SXRF) enables rapid scanning of large tissue areas with high resolution of elemental distributions. First, we used SXRF to map calcium, phosphorus, strontium and zinc distributions in great ape dentine and cementum. At higher resolution, we compared zinc and strontium distributions in cellular and acellular cementum in regions where clear incremental markings were expressed. We then mapped trace element distributions in fossil hominin dentine and cementum from the 1.55–1.65 million year old site of Koobi Fora, Kenya. Zinc, in particular, is a precise marker of cementum increments in great apes, and is retained in fossil hominin cementum, but does not correspond well with the more diffuse fluctuations observed in strontium distribution. Cementum is unusual among mineralized tissues in retaining so much zinc. This is known to reduce the acid solubility of hydroxyapatite and so may confer resistance to resorption by osteoclasts in the dynamic remodelling environment of the periodontal ligament and alveolar bone.